2019
DOI: 10.1029/2019gl084784
|View full text |Cite
|
Sign up to set email alerts
|

Plug Formation Imaged Beneath the Active Craters of Sakurajima Volcano With Muography

Abstract: Sakurajima Muography Observatory captured the formation of a volcanic plug beneath the Showa crater with a spatial resolution of ∼60 m in accordance with the end of the eruption episode of Showa crater and the reactivation of Minamidake crater. The increase of average density was observed with above 3 σ standard deviation for both above the floor of Minamidake crater and beneath the floor of Showa crater, respectively, being interpreted as volcanic ejecta deposition and the formation of a volcanic plug lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…Muography observation system at Sakurajima volcano. The muography observation system (MOS) 4 was installed at Sakurajima Muography Observatory (SMO) 22 . Figure 1(A-D) respectively show the location of the measurement site, a topographic map of the measurement site, and a cross-sectional view of Sakurajima volcano.…”
Section: Resultsmentioning
confidence: 99%
“…Muography observation system at Sakurajima volcano. The muography observation system (MOS) 4 was installed at Sakurajima Muography Observatory (SMO) 22 . Figure 1(A-D) respectively show the location of the measurement site, a topographic map of the measurement site, and a cross-sectional view of Sakurajima volcano.…”
Section: Resultsmentioning
confidence: 99%
“…The burial mound was originally surrounded by a double moat, but most of this moat was buried in the past, and only a part of it currently remains. The landslide deposits originating from the sediments in the moat were dated, and the results were 1420-1510 CE using a method of C 14 dating (Sangawa and Miyazaki, 2001). Since it is known that the Fushimi earthquake occurred in 1596, this burial mound collapse was thought to have been triggered by this earthquake (Sangawa and Miyazaki, 2001).…”
Section: Observationmentioning
confidence: 99%
“…The result is a pattern of the contrast in the density distribution inside the objects, which is projected onto a 2-dimensional plane. Muography has been applied to the imaging of the internal structure of volcanoes (Tanaka et al, 2007(Tanaka et al, , 2009(Tanaka et al, , 2014Lesparre et al, 2012;Oláh et al, 2019), cultural heritage sites, including the Giza pyramids (Cheops and Chephren), Egypt, the Prambanan temples, Indonesia, Mount Echia, Italy, and Santa Maria del Fiore, Italy (Alvarez et al, 1970;Hanazato and Tanaka, 2016;Tanaka and Ohshiro, 2016;Morishima et al, 2017;Guardincerri et al, 2018;Cimmino et al 2019), industrial plants (Tanaka, 2013), and other natural (Tanaka et al, 2011;Oláh et al, 2012;Schouten, 2018) and man-made structures (Mahon et al, 2018). Prior works have focused on searching for undiscovered chambers or the total weight of the heritage site.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of muography has already been demonstrated for volcano imaging thanks to the recent progress in the development of observation instruments [21][22][23][24][25][26][27][28][29][30] and imaging techniques [31][32][33][34] . Various volcanic phenomena, such as magma ascent and descent 35 , the degassing process 36 , plug formation 37 , magma intrusion into lava domes 38 , tectonic evolution 39 , hydrothermal processes 40,41 or long-term tephra deposition 42 , have already been measured with muographic imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Although this muographic measurement of tephra thickness demonstrated that muography could provide useful input for the determination of the magnitude and intensity of eruptions, the limited time resolution of the experiment was not sufficient to reveal the hydrogeomorphic changes which occurred on the volcanic edifice. In this work, we exploit the technological advantages, specifically the upgraded detection acceptance and angular resolution, of the Multi-wire-proportional-chamber (MWPC)-based Muography Observation System (MMOS) 33,37,43 of Sakurajima Muography Observatory (SMO) 33,34,37,42 to observe the short-term erosions of the volcanic edifice that can weaken and destabilize the upper parts of the volcano. Muographic monitoring of hydrogeomorphic responses to the disturbances of volcano landscapes may contribute to the assessment of the threats posed by indirect volcanic hazards.…”
Section: Introductionmentioning
confidence: 99%